2005
DOI: 10.1002/pen.20297
|View full text |Cite
|
Sign up to set email alerts
|

Oriented crystallization and mechanical properties of polypropylene nucleated on fibrillated polytetrafluoroethylene scaffolds

Abstract: It is known that friction deposited polytetrafluoroethylene (PTFE) layers are able to nucleate crystallization of thin films of isotactic polypropylene (iPP). In order to investigate the influence of PTFE on the crystallization behavior and morphology of iPP in bulk, PTFE-particles of two different sizes in various concentrations were melt-blended with iPP and subsequently processed by injection molding. For one size of particles, high resolution scanning electron microscopy (HR-SEM) showed the presence of a P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 31 publications
1
8
0
1
Order By: Relevance
“…In the past, PTFE was used to improve tribological properties of various polymers [19], although without the intention of deforming PTFE grains into fibrils. However, the formation of fibrils from PTFE during shearing has been noticed in other studies [20][21][22]. PTFE can deform into high-aspect-ratio fibrillar structures under loading conditions to dissipate energy and stabilize a crack tip by bridging, forming interconnected physically networks [23].…”
Section: Introductionmentioning
confidence: 86%
“…In the past, PTFE was used to improve tribological properties of various polymers [19], although without the intention of deforming PTFE grains into fibrils. However, the formation of fibrils from PTFE during shearing has been noticed in other studies [20][21][22]. PTFE can deform into high-aspect-ratio fibrillar structures under loading conditions to dissipate energy and stabilize a crack tip by bridging, forming interconnected physically networks [23].…”
Section: Introductionmentioning
confidence: 86%
“…15 Nascent powder of poly(tetrafluoroethylene) is another example of crystalline polymer with very low level of macromolecular chains entanglements. This polymer is easy deformable and fibrillated under the modest shear conditions during abrading as it was shown nearly 50 years ago by Geil et al, 16 when PTFE powder is fibrillated to form scaffolds 17 or mixed as a paste with lubricating liquid at 35 8C. 18 There are reports about the application of PTFE emulsion and powders at a low concentration, below 1% as nucleating agent for crystallization of other polymers.…”
mentioning
confidence: 95%
“…In this study we explored the unique characteristic of virgin, i.e., as‐polymerized PTFE to readily deform below its melting temperature, even under modest shear, to yield virtually endless fibrils of nanoscopic width—a well‐known phenomenon13 that forms the basis for the production of porous, so‐called expanded PTFE, better known as Goretex®14–16—to in situ create an ultra‐large, oriented surface that could provide the previously discussed beneficial nucleating substrate. Previous attempts by Van der Meer et al17 already demonstrated the potential of this approach in their study of compounding isotactic polypropylene (i‐PP) with particles of PTFE of different sizes and molecular weights. These authors once more showed that PTFE of high molecular weight indeed can be deformed into fibrillar scaffolds, onto which i‐PP was found to nucleate, leading to an improvement of selected mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…These authors once more showed that PTFE of high molecular weight indeed can be deformed into fibrillar scaffolds, onto which i‐PP was found to nucleate, leading to an improvement of selected mechanical properties. Here we report an expansion of the previous work,17 in which we employed suspensions of fine particles of virgin ultra‐high molecular weight PTFE. The latter were blended and subjected to controlled shear during compounding below the melting temperature of PTFE, with five common thermoplastic bulk polymers, i.e., i‐PP, high‐density polyethylene (HDPE), polyoxymethylene (POM), polyamide 12 (PA12), and poly(ethylene terephthalate) (PET), for which efficient nucleation of some remains a challenge 18–22.…”
Section: Introductionmentioning
confidence: 99%